2021
DOI: 10.3390/cells10020361
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A-Mediated Septin7 Phosphorylation Disrupts Septin Filaments and Ciliogenesis

Abstract: Septins are GTP-binding proteins that form heteromeric filaments for proper cell growth and migration. Among the septins, septin7 (SEPT7) is an important component of all septin filaments. Here we show that protein kinase A (PKA) phosphorylates SEPT7 at Thr197, thus disrupting septin filament dynamics and ciliogenesis. The Thr197 residue of SEPT7, a PKA phosphorylating site, was conserved among different species. Treatment with cAMP or overexpression of PKA catalytic subunit (PKACA2) induced SEPT7 phosphorylat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Our study found that SEPT6 inhibited the ubiquitin-coding gene UBC expression, affected the expression level of downstream cell proliferation-related genes, and thus affected the malignant of prostate cancer. Posttranslational modification plays an important role in regulating the Septin-septin interaction and controlling the formation of high-order septin complexes, and such modifications include SUMOylation, acetylation, ubiquitination, and phosphorylation [30]. The covalence modification of proteins by ubiquitination is the main regulatory mechanism of protein degradation and quality control, endocytosis, vesicle transport, cell cycle control, stress response, DNA repair, growth factor signal transduction, transcription, gene silencing, and other biological fields [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that SEPT6 inhibited the ubiquitin-coding gene UBC expression, affected the expression level of downstream cell proliferation-related genes, and thus affected the malignant of prostate cancer. Posttranslational modification plays an important role in regulating the Septin-septin interaction and controlling the formation of high-order septin complexes, and such modifications include SUMOylation, acetylation, ubiquitination, and phosphorylation [30]. The covalence modification of proteins by ubiquitination is the main regulatory mechanism of protein degradation and quality control, endocytosis, vesicle transport, cell cycle control, stress response, DNA repair, growth factor signal transduction, transcription, gene silencing, and other biological fields [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen‐activated protein kinase‐activated protein kinase 5 (MAPKAPK5 or MK5) of the MAPKAPK family is an in vivo Septin 8 interactor with in vitro phosphorylation sites at Ser242 and Ser271 in the more C‐terminal region of Septin 8's GTP‐binding domain (Shiryaev, 2012). cAMP‐dependent protein kinase (PKA) of the PKA family phosphorylates human Septin 7 at Thr197 in vivo (Wang et al, 2021). This site is highly conserved in mammals, and the PKA target motif resides in human Septins 2, 3, 4, 9, 10, 11, 12, and 14 (Wang et al, 2021).…”
Section: Septin‐associated Kinasesmentioning
confidence: 99%
“…cAMP‐dependent protein kinase (PKA) of the PKA family phosphorylates human Septin 7 at Thr197 in vivo (Wang et al, 2021). This site is highly conserved in mammals, and the PKA target motif resides in human Septins 2, 3, 4, 9, 10, 11, 12, and 14 (Wang et al, 2021). This motif on Septin 12 contains an in vivo PKA phosphorylation site at Ser198 (Shen et al, 2017).…”
Section: Septin‐associated Kinasesmentioning
confidence: 99%
See 2 more Smart Citations